Profitability, dividend policy, and capital structure as determinants of stock price in IDX30 firms (2022–2024) - Rizqiya Adha Riani; Hadi Suriono (Privietlab, 2026)
This study examines the partial and joint association between three fundamental financial signals — corporate profitability, dividend policy, and capital structure — and the stock price of blue-chip firms in the IDX30 index of the Indonesia Stock Exchange (IDX) during the post-pandemic period of 2022–2024. Drawing on signaling theory, trade-off theory, pecking-order theory, and the life-cycle theory of dividends, the study integrates three valuation-relevant signals — Return on Assets (ROA), Dividend Payout Ratio (DPR), and Debt-to-Equity Ratio (DER) — into a single explanatory framework that has rarely been examined within the IDX30 cohort. Using purposive sampling, a balanced short panel of 14 firms over three years (n = 42 firm-years, reduced to n = 38 after diagnostic outlier removal) was constructed from audited annual reports published through the official IDX website. The study employs pooled multiple-regression as the baseline specification while acknowledging the panel structure of the data; the limitations of pooled estimation for short panels and the implications for inference are discussed transparently in the methodology, and sector-stratified robustness is presented. Accounting predictors for year t are matched against the year-end closing price of year t, following common practice in prior Indonesian capital-market research; potential look-ahead implications are explicitly noted. The model is subjected to classical assumption tests (Kolmogorov-Smirnov for normality, VIF for multicollinearity, Glejser-style test for heteroscedasticity, and Durbin-Watson for autocorrelation). Results indicate that ROA is positively and significantly associated with stock price (β = 0.745, t = 13.35, p < 0.001), DPR is negatively and significantly associated with stock price (β = −0.558, t = −9.92, p < 0.001), and DER is positively and significantly associated with stock price (β = 0.573, t = 10.32, p < 0.001). Jointly, the three predictors explain 88.9% of the cross-sectional variance in stock price (F(3, 34) = 100.23, p < 0.001; Adj. R² = 0.889). The findings reinforce signaling theory for profitability, qualify the bird-in-hand interpretation of dividends in mature blue-chip firms (in line with life-cycle theory), and support a trade-off interpretation of moderate leverage in the IDX30 segment. Robustness checks and caveats relating to panel-data structure, sector heterogeneity (banks vs non-banks), and omitted growth-opportunity variables are discussed. The study contributes to the corporate-finance literature on emerging-market blue-chip equities and offers implications for investors, corporate managers, and capital-market policy.